HOW ISLAMIC LAW IS CONSTRUCTED TO ADDRESS CONFLICT VULNERABILITY ON SOCIAL MEDIA - Tarmizi, Tarmizi; Misbahuddin, Misbahuddin; Kurniati, Kurniati; Imran, Muh. Fadhil Abdillah (Institut Agama Islam Negeri Bone, 2024)
The presence of social media which facilitates interaction and provides openness of information not only produces positive impacts, but there are also negative impacts, such conflicts between social media users. This research aims to analyze the causes of conflicts easily occurring on social media and their implications as well as the response of Islamic law in providing solutions to conflicts on social media.Â By gathering information from online news sources along with relevant research findings, this study was conducted in a literary style. The collected data was then descriptively examined utilizing an Islamic legal framework. This study discovered that publishing about SARA topics, miscommunication, sensitivity, the propagation of misleading information, and cyberbullying were the main causes of conflict on social media. The conflict that occurred resulted in the opening of space for conflict and violence offline, loss of trust between social media users and the disintegration of the nation through the spread of fake news or mutual arguments, which had implications for the breakdown of unity and diversity in society. The construction of Islamic law exists as a response to conflicts that occur on social media, including mutual respect for fellow social media users, prioritizing tabayyun before receiving or forwarding news, being moderate towards differences of opinion and grounding the concept of Islamic social values as a construction of Islamic legal thought in answering problems based on digitalization.